The fine structure of microwave-induced magneto-oscillations in photoconductivity of the two-dimensional electron system formed on a liquid-helium surface: Электроны и ионы над/в сверхтекучем гелии - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The influence of the inelastic nature of electron scattering by surface excitations of liquid helium (ripplons) on the shape of magnetoconductivity oscillations induced by resonance microwave (MW) excitation is theoretically studied. The MW field provides a substantial filling of the first excited surface subband which sparks off inter-subband electron scattering by ripplons. This scattering is the origin of magneto-oscillations in the momentum relaxation rate. The inelastic effect becomes important when the energy of a ripplon involved compares with the collision broadening of Landau levels. Usually, such a condition is realized only at sufficiently high magnetic fields. On the contrary, the inelastic nature of inter-subband scattering is shown to be more important in a lower magnetic field range because of the new enhancement factor: the ratio of the intersubband transition frequency to the cyclotron frequency. This inelastic effect affects strongly the shape of conductivity oscillations which acquires an additional wavy feature (a mixture of splitting and inversion) in the vicinity of the level-matching points where the above noted ratio is close to an integer.